Infestation Level of Gastrointestinal Helminth in Swamp Buffalo (Bubalus bubalis Linn.) in Jati Agung District Lampung Selatan Regency - Achmad Barkah; Madi Hartono; Purnama Edy Santosa; Muhammad Mirandy Pratama Sirat (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2021)
The research was conducted at Jati Agung District Lampung Selatan Regency on December 2019, aimed to know infestation levels of gastrointestinal helminths on Mud Bufallo. The research used cencus method. Data collection has been done by taking all faecal samples from 80 Mud Bufallo at 6 village in Jati Agung District. Faecal samples examination checked with Mc. Master and Sendimentation test at Lampung Veterinary Hall. Data were analyzed descriptively. The results showed that of the 80 buffalo faeces samples examined, 23 samples (28.75%) were positively infested with gastrointestinal helminths in both single and multi-species infestations. The highest infestation found in Sinar Rejeki village about 100% and the lowest infestation found in Jatimulyo village about 18,51%. Helmiths species that found in Mud Bufallo are from Trematode class (Paramphistomum sp.) Nematode class (Toxocara sp., Bunostomum sp., Strongyloides sp., Haemonchus sp., Oesophagustomum sp., Trichostrongylus sp., and Mecistocirrus sp.), and Cestode class (Moniezia sp.).